2012
DOI: 10.1016/j.aim.2011.10.024
|View full text |Cite
|
Sign up to set email alerts
|

Higher index theory for certain expanders and Gromov monster groups, I

Abstract: In this paper, the first of a series of two, we continue the study of higher index theory for expanders. We prove that if a sequence of graphs is an expander and the girth of the graphs tends to infinity, then the coarse Baum-Connes assembly map is injective, but not surjective, for the associated metric space X.Expanders with this girth property are a necessary ingredient in the construction of the so-called 'Gromov monster' groups that (coarsely) contain expanders in their Cayley graphs. We use this connecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
122
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 97 publications
(123 citation statements)
references
References 36 publications
1
122
0
Order By: Relevance
“…From this, we then construct an operator that is not a ghost operator, but is ghostly on certain parts of the boundary. A tracelike argument, similar to those of [Hig99,WY12] then allows us to conclude that the boundary coarse Baum-Connes conjecture fails to be surjective for the space Y .…”
Section: A Counterexample To the Boundary Conjecturementioning
confidence: 99%
See 3 more Smart Citations
“…From this, we then construct an operator that is not a ghost operator, but is ghostly on certain parts of the boundary. A tracelike argument, similar to those of [Hig99,WY12] then allows us to conclude that the boundary coarse Baum-Connes conjecture fails to be surjective for the space Y .…”
Section: A Counterexample To the Boundary Conjecturementioning
confidence: 99%
“…K for any compact operator [WY12]. As these differ under T r, they cannot possibly be equal in K 0 (I G ).…”
Section: Proofmentioning
confidence: 99%
See 2 more Smart Citations
“…This problem is related to a question by J. Roe [Roe03] to define 'coarse property (T). ' R. Willett and G. Yu [WY12a], [WY12b] have studied the maximal coarse BaumConnes conjecture and introduced the notion of geometric property (T) for a (coarse) disjoint union of uniformly locally finite and finite graphs, which is stronger than being an expander sequence. They have showed that this property is an obstruction to the surjectivity of the maximal coarse Baum-Connes assembly map, and that a box space G has geometric property (T) if and only if G possesses property (T).…”
Section: Introductionmentioning
confidence: 99%